Inflammasome Signaling and Other Factors Implicated in Atherosclerosis Development and Progression - Nazarian-Samani, Zeinab; Sewell, Robert D. E.; Rafieian-Kopaei, Mahmoud (Current Pharmaceutical Design, 2020)
Chronic inflammation plays an extensive role in the onset and progression of metabolic disorders such as atherosclerosis, type 2 diabetes, gout and obesity. Atherosclerosis accounts for up to 70% mortality in patients with type 2 diabetes and is also a chronic condition that causes atrial stenosis due to a lipometabolism imbalance. The purpose of this article is to consider the inflammatory factors implicated in atherosclerosis and their role in the development and progression of this vascular disease. The inflammasome signaling pathway is an important inflammatory mechanism involved in the development of atherosclerosis. The most important inflammasome pathway in this respect is the NLRP3 inflammasome (Nucleotide-binding oligomerization domain (NOD)-like receptor with a pyrin domain 3), whose activation leads to the generation of important inflammatory cytokines including interleukins 1β and 18 (IL-1β and 18). The activities of these mature cytokines and inflammatory factors produced by other inflammatory pathways lead to arterial inflammation and eventually arterial occlusion, which can result in life-threatening complications such as myocardial infarction and stroke. Therefore, it is essential to seek out more precise mechanisms for the activation of inflammasomes and other inflammatory pathways for the development of therapeutic strategies of atherosclerosis.
Keywords: inflammation